An Analysis of Students’ Perception in Using Whatsapp as Media for Learning English during Covid 19 Pandemic at SMAN 1 Kecamatan Guguak - Inayatul Fitri; Yuli Tiarina (Journal of English Language Teaching, 2021)
This study aims to find out students' perceptions about the use of the Whatsapp application as media for learning English during the covid 19 pandemics in SMAN 1 Kecamatan Guguak. The sample of this study was the eleventh-grade students of SMAN 1 Kecamatan Guguak. The sample was carried out using the proportional random sampling method. The number of samples in this study was 177 students. Data was collected by means of a questionnaire and strengthened by interviews. This research is descriptive research with a quantitative approach. The results of this study indicate that students' perceptions of the use of WhatsApp as an English learning media are good. The average score of 3.72% evidence this, and the respondent's level of achievement is 92.90% in the good category.